Manfaat Youtube Dalam Dakwah Keagamaan Era Kontemporer - Yan Nurcahya; M Kautsar Thariq Syah; Deri Sugiarto; Dandie Hambaliana (AT-TAWASUL, 2025)
The As one of the favorite social media applications in the modern era, it has a history that has skyrocketed in the use of everyday society. Currently, with the intelligence of society, information technology and changes in religious practices provide deeper insight into how modern society, especially Muslims, adapt to technological developments in carrying out their worship. This study collects data from websites that discuss the digital religious application industry and its impact with a concentration on the Youtube application. The use of Youtube social media in the contemporary era has a significant impact on the spread of Islam, religious understanding, social improvement. Global Reach: YouTube allows da'wah content to be accessed by people around the world without being limited by space and time.